Maternal Health Services in Pakistan - Asma Ilyas (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Women must be provided with necessary health services for a child’s good health and future during pregnancy. Women’s health has experienced a considerable epidemiological change during the past several decades. Maternal well-being and health affect not only the developed world but predominantly the developing nations. Differences in resource allocation between industrialized and developing countries ultimately led to notable differences in pregnancy complications and deaths. Aim: To investigate these barriers. A literature review was carried out to address this research topic. Methodology: Six online databases AMED, CINAHL PLUS, PUBMED, MEDLINE, COCHRANE LIBRARY and SCIENCE DIRECT were used for a preliminary search that yielded 6353 articles. No grey literature was discovered due to time restrictions. Seven publications were discovered to be eligible for inclusion in the literature review after carefully reading, analysing, and evaluating them with the help of critical appraisal techniques. After the initially searched articles were filtered using robust inclusion and exclusion criteria. Findings: Data were taken from different sources like the Pakistan Demographic and Health Surveys (PDHSs), WHO, and a comparison was made with the findings from different factors. The analysis concentrates on women of Pakistan having maternal health issues and maternal health services. The Critical Appraisal Skills Program (CASP) is used for the assessment and qualitative analysisof this study. Practical implications: By addressing the issues highlighted in this paper there appears to be substantial room for improvements in Pakistan’s pregnancy outcomes. This review provides a better understanding of the risk factors determining maternal mortality in Pakistan.Public awareness is important as this paper almost covered the different platforms which are working on maternal health servicesto aware the society. To promote maternal health messages and encourage pregnant women to receive maternal healthcare services, policymakers, healthcare professionals, and health organizations can adopt a variety of campaigns. Results: This study discussed the impact of different factorswhich effect on maternal health. Different factors are associated with utilizing maternal healthcare services at antenatal care and delivery stages of pregnancy in Pakistan. This review concentrated on the economic and social vulnerability of pregnant women and emphasized the importance of parallel, more all-encompassing initiatives, like poverty reduction and women’s empowerment. Poor maternal health in Pakistan has many root causes, including undernourishment of young girls, early marriage, high fertility rates, and unmet contraceptive needs. Conclusion: The key factors influencing women’s hesitation and refusal to use the health facilities in Pakistan include structural hurdles, maternal knowledge and education levels, and men’s dominance in decision-making, according to the themes drawn from the literature. Keywords: Pregnant women, Maternal health, Ante-natal care, Pakistan,Demographic and health surveys,